Management of Rett Syndrome in the Controlled Multisensory (Snoezelen) Environment. A Review with Three Case Stories - Meir Lotan (The Scientific World Journal)
Rett syndrome (RS) is a neurological disorder resulting from an X-linked dominant mutation. It is characterized by a variety of physical and perceptual disabilities, resulting in a need for continuous intervention programs to be administered on a regular basis throughout life. Many of these individuals with RS show fear of movement and, therefore, find it hard to accept external facilitation (so common in physical therapy intervention). In a search for novel intervention techniques that might improve their ability to cope with difficulties in daily situations, while also reducing their difficulty in handling motion inflicted by an external physical facilitator, we examined the use of the Snoezelen room. The Snoezelen, also known as the controlled multisensory environment, can provide a soothing atmosphere that appeals to the individual with RS, while at the same time it can improve physical, sensorial, and functional abilities. This article suggests various intervention goals that are appropriate for individuals with RS at different stages of the disorder. Since the management of young children with RS in the multisensory environment has been discussed at length in the past, this article will mainly describe intervention with adults with RS, focusing on three case stories. The present article reviews the available scientific materials on the topic of Snoezelen, incorporating clinical knowledge in the field of RS and suggesting this approach as an appropriate intervention method for this population.